The change of youth unemployment based on the concept of precariat - Szabó, Fanni; Röfi, Mónika (Acta Agraria Debreceniensis, 2014)
Youth unemployment is a hot potato issue worldwide, including Hungary and its reduction is a major focal point in every country. Today’s labour market is characterized by uncertainties and unpredictability while flexibility, project-related employment are emphasized, which pose different expectations on employees than before. This phenomenon is included in the concept of precariat. In the present study the labour market status, future potentials and options of youths in the Derecske district of Hungary are described.